ASSESSING THE TECHNICAL SKILLS OF TVET INSTRUCTORS IN RIVERS STATE, NIGERIA: IMPLICATION FOR STUDENT'S INTEREST IN TECHNICAL EDUCATION - Cornelius James, Igbikialabo (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Due to the emphasis placed on developing graduates with technical and vocational skills, instructors in the TVET domain are expected to possess a high level of knowledge and expertise. As a result, the emphasis placed on the quality of TVET instructors in Nigeria has become an intriguing issue that warrants additional research. The present study examined the technical skills of TVET instructors in River State, Nigeria. Ninety-six technical and vocational education instructors pooled from five government technical colleges in River State participated in the study. They completed a questionnaire measuring technical competency in six dimensions. The result revealed a high technical competence outcome for material and application (75.5%), work planning (71%), practical pedagogy (66.7%), and theoretical instructional strategy (59.4%). Also, the findings indicated a low technical competency for maintenance (15.6%) and students' workshop management (18.1%). The result has implications for developing students' interest in the TVET program in Nigeria.